Variation in fibres and vessel elements of delonix regia (caesalpiniaceae) (1993)
Variation in fibres and vessel elements of the secondary xylem of Delonix regia has been investigated by light microscopy. Tills work clearly establishes inter-positional variation in the dimensions, particularly of the fibres both axially and radially. Generally, the longest and widest fibres are recorded at the breast height of 1.39 m from the base of the plant. The widest but shortest fibres occur towards the pith while the thinnest but longest fibres are found towards the periphery. The widest and longest vessels are also found at the breast height of 1.30 m from the base of the plant. The importance of these variable characters in the taxonomy of the taxon is discussed.